THE EFFECT OF OWNERSHIP STRUCTURE ON INVESTMENT EFFICIENCY (CASE STUDY IN NON FINANCIAL FIRMS LISTED ON INDONESIA STOCK EXCHANGE IN 2015-2017) - Faviola Lady Anela; Andrian Budi Prasetyo (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
The objective of this study is to investigate whether ownership structure and corporate governance affecting the efficiency of investment of listed non-financial firms in Indonesia. Ownership concentration, managerial ownership, management stock option, and mutual funds ownership used as independent variables in this study. Meanwhile, the dependent variable in the research is investment efficiency. Regression analysis is used as a method in analyzing secondary data obtained by using purposive sampling method. Secondary data used in research sourced from the financial statements and annual reports of non-financial companies listed on the Indonesia Stock Exchange in 2015-2017. The result of this research indicates that ownership concentration does not have a significant influence towards investment efficiency. This result also shows that each of managerial ownership and management stock options positively influence investment efficiency. Furthermore, mutual funds’ ownership is proven that positively influence the investment efficiency